Association Between Papillary Thyroid Carcinoma and Vertebral Fracture - Otani, Hazuki; Notsu, Masakazu; Yamauchi, Mika; Nawata, Kiyoko; Kanasaki, Keizo (Hormone and Metabolic Research, 2023)
Suppression of TSH levels associated with levothyroxine treatment is a known risk factor for fracture. However, it is unclear whether patients with papillary thyroid carcinoma (PTC) have a higher risk of vertebral fracture (VF) before TSH suppression. The aim of the study was to examine whether the risk of VF is higher in PTC than in healthy subjects. A hospital-based, matched case-control study was conducted comparing PTC and healthy individuals. We enrolled 43 postoperative patients with PTC scheduled for radioiodine therapy and 43 age- and sex-matched healthy controls. Serum and urinary biological parameters, bone mineral density (BMD), and presence of VFs were evaluated in both groups. We compared these indices using χ2 and Mann–Whitney U-test and analyzed the association between PTC and VF by logistic regression analysis. The PTC group had higher BMI, HbA1c and phosphorus, and lower intact PTH than the control group. Lumbar and femoral neck BMD did not differ between the two groups. Prevalence of VFs was significantly higher in the PTC group (44.1%) than in the control group (16.3%). Multivariate logistic regression analyses adjusted for age, sex, and BMI identified PTC as being associated with the presence of VFs (odds ratio, 5.63; 95% confidence interval: 1.82 to 17.5). This relationship remained significant after additional adjustment for HbA1c and BMD. There is an association between PTC and a risk of VF independent of sex, BMI, glucose metabolism, and BMD, suggesting the importance of fracture risk assessment before TSH suppression.
Keywords: thyroid cancer; osteoporosis; osteopenia; thyroid-stimulating hormone